Investigating Particularized Conversational Implicatures in a Sitcom Serials - Zuraida Supri, Ida; C M Simatupang, Ervina (International Journal of Psychosocial Rehabilitation, 2020)
Misunderstanding may happen when the utterance of one of the participants does not fulfill the cooperative principles of communication. This may result in an unpleasant situation, such as feeling offended, a bad impression, or a misjudgement. The above misunderstanding can be avoided if the partner speaking understands the message intended to convey despite the violation of cooperative principles. This research aims at identifying particularized conversational implicatures in the assertive illocutionary acts found in a sitcom serial. The results show particularized conversational implicature is found in three types of assertive illocutionary acts.